2022
DOI: 10.1038/s41598-022-21993-9
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary spastic paraplegia SPG13 mutation increases structural stability and ATPase activity of human mitochondrial chaperonin

Abstract: Human mitochondrial chaperonin mHsp60 is broadly associated with various human health conditions and the V72I mutation in mHsp60 causes a form of hereditary spastic paraplegia, a neurodegenerative disease. The main function of mHsp60 is to assist folding of mitochondrial proteins in an ATP-dependent manner. In this study, we unexpectedly found that mutant mHsp60V72I was more stable structurally and more active in the ATPase activity than the wildtype. Analysis of our recently solved cryo-EM structure of mHsp60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…1a). Importantly, the V72I mutation retains some client refolding activity in vitro 43 , suggesting that general features of the mtHsp60 chaperone cycle are preserved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a). Importantly, the V72I mutation retains some client refolding activity in vitro 43 , suggesting that general features of the mtHsp60 chaperone cycle are preserved.…”
Section: Resultsmentioning
confidence: 99%
“…The hereditary spastic paraplegia variant mtHsp60 V72I forms stable heptamers and retains significant chaperone activity Wild type mtHsp60 heptamers are unstable in the absence of mtHsp10 in vitro, and readily dissociate into monomers at low concentration or temperature, or when incubated with nucleotide 39 , thereby complicating efforts to characterize the mtHsp60 chaperone cycle. To facilitate structural studies of mtHsp60, we focused on the previously identified mtHsp60 V72I variant that is associated with hereditary spastic paraplegia SPG13 26,29 , and is reported to have increased oligomeric stability 43 . Residue V72 (numbering corresponds to the mature mtHsp60 protein after cleavage of the mitochondrial import sequence) is located in the equatorial domain of mtHsp60 and packs into its hydrophobic core, but does not contact the ATP binding pocket (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation